Sexual behaviour, contraceptive practice and reproductive health among school adolescents in rural Transkei - Buga, G A; Amoko, D H; Ncayiyana, D J (South African medical journal, 1996)
To determine the patterns of sexual maturation, sexual behaviour, contraceptive practice and reproductive health among Transkeian adolescents. Cross-sectional descriptive study, using self administered questionnaires. Twenty-six schools in 22 rural districts of the Transkei region of the Eastern Cape. Standard 5, 6 and 7 pupils of both sexes. Demographic and social characteristics, maturational and sexual behavioural milestones, and the prevalence of contraceptive use, pregnancies and sexually transmitted diseases (STDs). Data from 1,072 girls and 903 boys were analysed. The mean ages (+/-SD) of the girls and boys were 15.29 +/- 1.89 and 16.25 +/- 2.05 years, respectively. Menarche and semenarche occurred at 13.90 +/- 1.23 and 15.12 +/- 1.58 years in girls and boys, respectively. Overall, 76% of the girls and 90.1% of the boys in this survey were already sexually experienced. The age of initiation of sexual activity was positively correlated with the age of first dating and the age of menarche and semenarche. The boys initiated sexual activity at an earlier age (13.43 v. 14.86 years, P = 0.0000), had sexual intercourse more regularly (61.6% v. 42.3%, P = 0.0000) and more frequently, and had more lifetime sexual partners (mean of 3.27 v. 1.35, P = 0.0000) than the girls did. Nearly twice as many sexually experienced boys as girls had a history of STD (48% v. 25%, P = 0.0000) and, of these, 19.1% of the boys and 6.5% of the girls had a history of genital ulcer disease. The prevalence of whether contraceptives had ever been used was only 23% among sexually experienced girls and, of these, only 19.4% used condoms. Surprisingly, 62.1% of the sexually experienced boys had used condoms, and of these nearly one-third enjoyed using them. The prevalence of adolescent schoolgirl pregnancy was 31.3%. Sexual maturation occurs at an earlier age than previously among rural Transkeian adolescents. This is associated with early initiation and a high level of sexual activity, low contraceptive usage, and a high rate of adolescent pregnancy and STDs, which therefore expose adolescents to a high risk of HIV infection.